Law Enforcement Against Criminal Acts of Using Other People's Voting Rights in Elections - Zefrizal Zefrizal (International Journal Reglement & Society (IJRS), 2022)
Election law issues can be said to be more complex. In addition to the many categories of problems, the implementation of handling election legal issues also involves many institutions/institutions. The type of research used in this research is normative juridical. The nature of this research is descriptive analytical. As for what is meant by descriptive analytical research is a research that can describe in detail and systematically about the object under study. Secondary legal materials include explanations of primary legal materials in the form of expert doctrine found in books, journals, and websites. The results of the study show that the provisions of Article 533 of Law Number 7 of 2017 concerning General Elections state that "Everyone who intentionally at the time of voting claims to be someone else and/or casts his vote more than 1 (one) time in 1 (one) time. TPS or more shall be sentenced to a maximum imprisonment of 1 (one) year 6 (six) months and a maximum fine of Rp. 48,000,000.00 (forty eight million rupiah)”. Law enforcement against the general election crime is carried out by the Election Supervisory Body (BAWASLU) whose task is to prevent and take action against election violations and election disputes as referred to in Article 93 letter b of Law no. 7 of 2017 concerning General Elections. who then cooperated with the police, one of the tasks of the Indonesian National Police in dealing with criminal acts of general election, namely conducting an investigation of election crimes that were reported to the National Police through Bawaslu, after the report found elements of a general election crime and also if proven the existence of an election crime, a prosecution can be carried out by the Prosecutor's Office, the demands given to the perpetrator of an election crime are in accordance with the violation that contains elements of the criminal act committed